The Effect of Aloe Vera Hydrogel on the Process of Burn Healing: A Systematic Review and Meta-Analysis - Rahmat Effan Fahri Mahendra; Asmat Burhan (Indonesian Science Media, 2024)
Background: Heat, chemicals, radiation, electricity, and fire can burn skin. Aloevera, among other treatments, helps speed up burn healing, especially first- and second-degree burns. This article examines if aloevera speeds burn recovery. Aims: In this investigation, the effect of aloevera on the progression of first- and second-degree burns was evaluated. Design and Methods: This systematic review and meta-analysis examined ProQuest, PubMed, Scopus, Web of Science, ScienceDirect, and CINAHL studies from January 2016 to March 2021. RevMan 5.4.1 and R-Studio meta-analysis risk of bias 2.0. Results: An examination of residual heterogeneity in 278 people over 4 trials revealed significant variations in wound healing, with an I2 value of 0%. The healing of burn wounds using aloevera showed a Standard Mean Difference (SMD) of 0.00, with a 95% Confidence Interval (CI) ranging from -0.46 to 0.47, indicating a strong level of significance. Conclusion: Aloevera's effect on the progression of first- and second-degree burns was the purpose of this research.